The PENSIEVE : psychological quasi-experimental neural study of induction efficacy of virtual environments - Bothma, T.J.D. (Theodorus Jan Daniel) (University of Pretoria, 2024)
Dissertation (MIS (Multimedia))--University of Pretoria, 2024.